Rapid tranquilization: An audit of Irish mental health nursing practice. (12th February 2018) - Nash, Michael; McDonagh, Caitriona; Culhane, Aisling; Noone, Imelda; Higgins, Agnes
Abstract: Rapid tranquillization is a pharmacological intervention sometimes employed in mental health care for the management of acute behavioural disturbance. It is a form of restrictive practice, which, along with seclusion and restraint, is a conventional and controversial intervention in the therapeutic management of risk in mental health settings. This study surveyed mental health nurses practice in rapid tranquillization. A self‐report questionnaire was utilized which addressed aspects such as definitions of rapid tranquillization, presence of rapid tranquillization policy, types of incidents where it is used and postintervention monitoring. The results demonstrate that rapid tranquillization is an intervention used in the management of acute behavioural disturbance in various mental health settings in Ireland. Respondents showed a basic understanding of rapid tranquillization as an intervention; however, some areas reported not having a specific rapid tranquillization policy. There was some evidence of a variation in postrapid tranquillization monitoring of psychiatric/mental health and physical health. Service user debriefing following rapid tranquillization was reported to be common; however, the content of this was not elaborated on. In the light of variations in practice, specific training and the development of rapid tranquillization policies are recommended.